Kropotkin and the anarchist intellectual tradition - Mac Laughlin, Jim (Pluto Press, 2016)
Rescues Kropotkin's philosophy of anarchism from the neglect that it has suffered in mainstream histories.
Keywords: Kropotkin, Petr Alekseevich, -- kni͡azʹ, -- 1842-1921.; Kropotkin, Petr Alekseevich, -- kni͡azʹ, -- 1842-1921; Kropotkin, Pëtr Alekseevič -- 1842-1921; Anarchism -- History.; Anarchists -- Russia -- Biography.; Anarchisme -- Histoire.; Anarchistes -- Russie -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Political.; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism.; Anarchism; Anarchists; Russia; Anarchismus; Politische Philosophie; Biographies; History; Biographies.